Regulation of Noncoding Transcriptome in Developing Photoreceptors by Rod Differentiation Factor NRL - Zelinger, Lina (Invest Ophthalmol Vis Sci, 2017)
PURPOSE: Transcriptome analysis by next generation sequencing allows qualitative and quantitative profiling of expression patterns associated with development and disease. However, most transcribed sequences do not encode proteins, and little is known about the functional relevance of noncoding (nc) transcriptome in neuronal subtypes. The goal of this study was to perform a comprehensive analysis of long noncoding (lncRNAs) and antisense (asRNAs) RNAs expressed in mouse retinal photoreceptors. METHODS: Transcriptomic profiles were generated at six developmental time points from flow-sorted Nrlp-GFP (rods) and Nrlp-GFP;Nrl(−/−) (S-cone like) mouse photoreceptors. Bioinformatic analysis was performed to identify novel noncoding transcripts and assess their regulation by rod differentiation factor neural retina leucine zipper (NRL). In situ hybridization (ISH) was used for validation and cellular localization. RESULTS: NcRNA profiles demonstrated dynamic yet specific expression signature and coexpression clusters during rod development. In addition to currently annotated 586 lncRNAs and 454 asRNAs, we identified 1037 lncRNAs and 243 asRNAs by de novo assembly. Of these, 119 lncRNAs showed altered expression in the absence of NRL and included NRL binding sites in their promoter/enhancer regions. ISH studies validated the expression of 24 lncRNAs (including 12 previously unannotated) and 4 asRNAs in photoreceptors. Coexpression analysis demonstrated 63 functional modules and 209 significant antisense-gene correlations, allowing us to predict possible role of these lncRNAs in rods. CONCLUSIONS: Our studies reveal coregulation of coding and noncoding transcripts in rod photoreceptors by NRL and establish the framework for deciphering the function of ncRNAs during retinal development.